Some Poisonous Medicinal Plants Used for Abortion in Sagar Region of Central India - Choubey, V. B.; Khare, P. K. (Indian Forester, 2014)
A preliminarily survey was conducted for poisonous and indigenous medicinal plants in tropical dry deciduous forests of Sagar region in Central India. A total of 14 plant species belonging to 13 families and 13 genera were collected. Among them four were herbs, two shrubs and eight were tree species. These plants species are used traditionally as indigenous medicines in many diseases. Name of species, its family, habit, toxic principles, chemical constituents of toxic part, and medicinal uses are described.